Feeding Preference of Larvae and Adults of Zigzag Beetle on Sucking Insect Pests of Brinjal Under Lab. Condition at Tando Jam - Khoso, Abdul Ghaffar; Khan, Mansab; Ahmed, Saeed (International Journal of Applied Sciences and Biotechnology, 2019)
Study was carried out on Feeding Preference of Larvae and Adults of Zigzag Beetle on Sucking Insect Pests of Brinjal Under Laboratory Conditions in 2013 at Tando Jam. Observations on feeding preference of Zigzag beetle shows that the highest feeding consumption of first instar larvae of Zigzag beetle were consumed 9.28±1.47aphids/day. Similarly on whiteflies the feeding rate was 7.56±1.05, and on thrips 5.28±0.98. The mean highest consumption of 1st instar was recorded on aphids, and lowest on. Similarly in the second instar larva the mean highest consumption rate during 24 hours was recorded on aphids. 19.21±1.97 / day followed by whiteflies 13.39±2.82/day and thrips 10.36±1.89/day. In case of third instar larvae the maximum feeding rate was recorded on aphids 35.26±2.06/day followed by whiteflies. 23.15±2.45/day and thrips 16.36±3.82/day. The fourth instar larvae of Zigzag beetle was consumed 52.69±3.89aphids/day followed by whiteflies 39.64±3.02/day and thrips 26.85±5.56/day. While the feeding preference rate of both male and female adults of Zigzag beetle also observed. The male adults of Zigzag beetle was 61.17±4.67 aphids/ day. On whiteflies was 42.89±4.12. Similarly on thrips was 32.56±6.26 thrips/ day. The mean aphid consumption by female adults was more on aphids 72.34±5.33 / day followed by whiteflies 47.23±4.93/day and thrips 37.89±7.19/day. The overall data indicated that fourth instar larvae of Zigzag beetle was more voracious feeder of different sucking insect pests of brinjal as compare to 1st, 2nd and 3rd instar larvae and female adults of Zigzag beetle consumed more sucking pests of brinjal than male adults . However, there is no significant difference between both sexes. The data reveals that aphids was most preferred food and thrips was least preferred prey for Zigzag beetle.Int. J. Appl. Sci. Biotechnol. Vol 7(1): 27-30